2015
DOI: 10.1627/jpi.58.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrocarbon Structure on Steam Reforming over Ni/perovskite Catalyst

Abstract: Ni/perovskite-type oxide catalyst (Ni/La0.7Sr0.3AlO2.85: LSAO) shows high catalytic activity and low carbon formation during the steam reforming of aromatic hydrocarbons because of the high mobility of lattice oxygen in the support. The reaction mechanisms of the catalyst were investigated by characterizations and catalytic activity tests for steam reforming of various hydrocarbons including toluene, methylcyclohexane, and n-heptane. The catalytic performance was affected by the reactant structure, as revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Consequently, the rate of NO reduction by C x H y O z also decreases because the formation rate of C x H y O z decreases. Sr 0.3 AlO 3Àd ),26,27 we reported that hydrocarbons were oxidized by the lattice oxygen of La 0.7 Sr 0.3 -AlO 3Àd . The lattice oxygen of La 0.7 Sr 0.3 AlO 3Àd , having high mobility, can contribute to the surface reaction via release and restoration.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Consequently, the rate of NO reduction by C x H y O z also decreases because the formation rate of C x H y O z decreases. Sr 0.3 AlO 3Àd ),26,27 we reported that hydrocarbons were oxidized by the lattice oxygen of La 0.7 Sr 0.3 -AlO 3Àd . The lattice oxygen of La 0.7 Sr 0.3 AlO 3Àd , having high mobility, can contribute to the surface reaction via release and restoration.…”
mentioning
confidence: 94%
“…15,20,23,24 Results have shown that the lattice oxygen reacts with various hydrocarbons to form partially oxidized hydrocarbon species (C x H y O z : oxygenated species) on Sr-substituted LaAlO 3 . [25][26][27] Oxygenated species reacted with H 2 O as reductants to form H 2 . Then the lattice oxygen consumed is restored by H 2 O in atmosphere.…”
Section: Introductionmentioning
confidence: 99%